A microscopic elasto-plastic damage model for characterizing transverse responses of unidirectional fiber-reinforced polymer composites. (September 2020) - Li, N.; Chen, P.H.; Ling, X.
Abstract: A phenomenological-based micromechanical method, comprising the coupling of the matrix constitutive model and the cohesive zone (CZM) model at fiber-matrix interfaces, is presented to investigate the mechanical behaviors of unidirectional (UD) fiber-reinforced polymer (FRP) composites subjected to transverse tension and compression. The key point of this method is the establishment of a novel elasto-plastic damage constitutive model using a fracture plane based yield criterion. Both plastic deformation and progressive failure procedure is incorporated in the implicit simulation. Special focus is given to the determination of the input values of constituent material properties, suggesting that directly using the macroscopic matrix properties to characterize the mechanical responses at the microscale level may bring large discrepancies in homogenized stress-strain responses of UD composites. A parametrical study is also carried out to calibrate cohesive parameters. The numerical results, in good agreement with experimental measurements, clearly reveal the damage scenarios and the dominant failure mechanisms. It can be concluded that the debonding of the fiber-matrix interfaces is responsible for the ultimate transverse tensile strength, while compression failure is governed by two possible modes, i.e. matrix compressive failure if matrix failure firstly occurs, and matrix tensile and interface debonding failure when debonding initiates first. Besides, the distribution of fracture plane angles in matrix is examined to further validate the predictive capacity of the proposed model. Highlights: An elasto-plastic damage model is developed to capture fracture plane angle of epoxy matrix. Tensile and compressive failure mechanisms are analyzed from distribution of fracture plane angles at multi scales. Rationality of directly using macroscopic properties into microscale simulation is investigated.